Genetic stability in synthetic wheat accessions: cytogenetic evaluation as a support in breeding programs - Frizon,Patrícia (2017)
ABSTRACT: Synthetic wheat is developed by crossing tetraploid species ( Triticum turgidum , AABB) with a diploid species ( Aegilops tauschii , DD), followed by chromosome duplication through the use of colchicine to restore the resultant sterile hybrid to a fertile hexaploid plant. The main importance of producing synthetically improved wheat is to increase their genetic variability and to incorporate genes that code for resistance to biotic and abiotic stressors. This study aimed to evaluate the presence of micronuclei (MN) and the meiotic index (MI) in the tetrad phase in synthetic wheat accessions and cultivars ( Triticum aestivum ) stored at the Germplasm Bank of Embrapa Trigo (Brazil), in order to identify and select genetically stable accessions for plant improvement. Five plants were collected by genotype, prior to anthesis, and the tissues were fixed in Carnoy solution. Cytological slides were prepared by the smash method, and the cells were dyed with 1% acetocarmine and observed under an optical microscope. Presence of MN was observed in all genotypes analyzed, and variability of genetic stability was reported in the two years of analysis. In 2014, the highest MI of synthetic wheat accessions was 96.86% and the lowest was 46.32%. In 2015, the highest MI was 96.60% and the lowest was 47.96%. Based on the results, some genotypes were considered meiotically stable and suitable for use in wheat breeding programs.